Les approches interculturelles dans le système éducatif brésilien : entre immobilisme et transformations radicales - Abdeljalil Akkari; Camila Pompeu Da Silva (Recherches en Éducation)
This article aims to analyze the emergence of intercultural education in the Brazilian educational system. First, we try to trace the development of interethnic relations in the country. The heaviness of slavery and colonization will be pointed out. Then, the article addresses recent legislative measures to encourage the inclusion of diversity in education. Finally, the text focuses on intercultural approaches in teacher education and work. The Brazilian situation is interesting because there is both a continuing conservatism preventing intercultural legitimacy in school but at the same time a profound debate about cultural identities and the need to take into account all historical inequalities.